The Amendments to the Electoral Code Made by the 48th Parliament and their (In)Compliance with the Constitution - Slavov, Peter (Yearbook of the Law Department, 2022)
The 48-th Parliament (National Assembly) is likely to be remembered with the significant changes it undertook in the electoral legislation, whereas just a few days after the Parliament was formed these changes were initiated without the prior and required by law public discussion, impact assessment and analysis of the possibility to implement these changes by the election administration in the context of a short-lived Parliament and upcoming preliminary elections. The most significant changes in the Electoral Code (over 150 in total) were targeted at a radical change of the regulations for the so-called “machine voting”, whereas the machine counting of the votes and preferences was abolished and the receipts printed by the machines for each vote were called “ballots of machine voting”. These from now on had to be counted by hand, along with the preferences in them and the results had also to be summed up manually with those of the traditional voting with paper ballots and the results written down in a joint protocol. Other important changes refer to the abolition of the so-called “dark rooms” and their replacement with “screens” which had to guarantee the secrecy of voting along with video surveillance and recording of the process of counting the ballots after completion of the vote.